Legal Analysis of Marine Environmental Protection from Greenhouse Gas Emissions - Dianti Reres Rimbawati; Ria Tri Vinata (Asian Journal of Environmental Research, 2026)
Climate change due to drastic increases in greenhouse gas (GHG) emissions has damaged marine ecosystems through warming and acidification. This study aims to analyze the conformity of international law and the implementation of Indonesian national regulations in an effort to protect the marine environment from the impacts of anthropogenic GHG emissions. Using normative legal research methods, this study applies legislative and conceptual approaches to examine UNCLOS 1982, the Paris Agreement, the Environmental Management Law, and Presidential Regulation No. 110 of 2025. The results show that Article 192 of UNCLOS 1982 is now interpreted as a due diligence obligation that requires states to make maximum efforts to prevent marine pollution, including emissions released into the atmosphere. At the national level, Indonesia has made significant reforms through Presidential Regulation No. 110 of 2025 which allows for accelerated carbon trading without having to wait for the achievement of NDC targets. In addition, the enactment of Ministerial Regulation No. 1 of 2025 strengthens the technical governance of blue carbon as a mitigation instrument and economic asset. The study concludes that Indonesia has built a responsive legal foundation by integrating the Economic Value of Carbon into marine environmental protection. The implementation of MRV mechanisms and emissions certification demonstrates the state responsibility to fulfill international commitments. This legal harmonization is a prerequisite for slowing marine ecosystem degradation, safeguarding marine biodiversity, supporting food security for coastal communities, and advancing intergenerational environmental justice.  Nevertheless, consistency between economic acceleration and ecosystem integrity remains necessary to ensure sustainable marine conservation.